Pengelolaan Dana Zakat Kontemporer: Mengentas Kemiskinan dan Solusi Meningkatkan Perekonomian Bangsa - Muhammad Yazid (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2020)
This research was conducted with the aim to find out the management of zakat in poverty alleviation and to find a model of contemporary zakat management in solutions to improve the nation's economy. The research method used is descriptive qualitative. The results of the study show that the management of zakat can alleviate poverty through the East Java Prosperous Program in the form of productive zakat funds in the form of venture capital assistance, skills training, and provision of business tools. Productive zakat funds are not funds for consumption mustahiq, but to be used mustahiq in business and improve their quality so that the productive zakat funds are not only used up once, but can support the life of mustahiq in the future until he turns into muzakki. The management of zakat in a contemporary perspective in this study is intended that Baznas can work together with sharia cooperatives which together become amil zakat. This model of cooperation in managing zakat can certainly benefit various parties, especially for Baznas, sharia cooperatives, and micro-entrepreneurs.